Comparative analysis of populations of species of palms producing “chonta” in collective forests of the black community of Alto San Juan, Tadó, Chocó, Colombia - Murillo Hinestoza, Yirlesa; VargasPorras, Lady (Journal BioEtnia, 2014)
In 2010, a study of composition and richness was conducted in the towns of producing palms chonta in a collective forest located in the town of Tadó, Chocó, Colombia. These palms have been harvested to extract logs or long strips from their stems called chonta, which are suffering heavy human pressures leading to the decline of these populations. Systematic sampling were established in 191 plots of 10 x 10 m, equivalent to 1.91 hectares in 6 areas of sampling, of which Alto Chato got 43%, Manungará 23%, 18% Angostura, Carmelo 8% cap and Corcobado 4% each established plots, recording a total of 1480 individuals; of these, 525 fustal, 162 latizal and 793 brinzal belonging to Palma Meme Wettinia machinery, Palma Barrigona Iriartea deltoid, Don Pedrito Oneocarpus mapora, murrapo precatoria Euterpe, chappi Euterpe oleraceae and Palma Zancona Socratea exho- rriza, Mousetrap astrocaryum jauari Martius and Viejita NN. Wettinia machinery, recorded the highest number of individuals with 1039 equal to 70% of the total identified, followed by Iriartea deltoid and Socratea exhorriza with 8% each, contrary to Euterpe registration precatoria only 7 individuals, being the kind of lower abundance. The study shows that the pressure caused by the selective use of palm producers chonta in these communities has led to such populations are much more distant from population centers; in this order of idea, Wettinia machinery has been the most depressed species, however the amount of saplings (631) and latizal (97) can guarantee the supply of chonta in the área.